From theory to textual practice at high school: Challenges and perspectives - Lemos, Glícia Juliana Leandro (2023)
This article presents the results of a research that investigated the conception of text and textual production in High School. The study identified limitations and potentialities in students' writing through observation in the classroom, interviews, analysis of textual productions and other methodological approaches. The research used a qualitative methodology that involved bibliographic, documentary, and field research. The results revealed that pedagogical practices in textual production classes still reproduce an environment of teaching-learning with artificial and decontextualized production conditions, typical of school writing activities.